La Familia como Factor Protector en el Rendimiento Escolar de los Niños y Niñas de la Escuela Rosa Josefina Burneo de Burneo y la Intervención de El/La Trabajador/a Social - Acaro Vega, Carmen Melania (2016)
This work is part of a study at school Burnet Burnet Rosa Josefina in relation to Domestic Violence in children / as of 1st to 4th year of basic education as a determining factor in school performance, emotional state, behavior; aspect that hinders the integral development of children / as. The intervention of the worker / a Social on the issues in the field of education is imperative, since; through a methodological research process allowed to determine the causes and consequences that domestic violence in school performance and thus comply with the specific objective raised in this research and also design and implement a social action plan aimed at improve family life, with emphasis on the following topics: family functions, communication and peace in family, parental authority against children and domestic violence and school performance aimed at parents of 1st to 4th year basic education to strengthen family relationships and engaging family as a protective factor in school performance of children, damage and comply with the overall objective in this work. The main findings from research validates that school performance of children / as is fair to low due to domestic violence of psychological type that is generated in the home, pointing out that this problem is affecting their concentration in school and it has lowered self-esteem and interest in school causing an imbalance between their emotional state and their educational responsibilities, mostly agree that the main causes for domestic violence is generated are: alcoholism mainly parents, poor communication between parents, 5 accompanied infidelity misunderstandings, the difference of religion between the couple, unemployment and lack of money among family generating consequences such as poor performance, being one of the most visible consequences and that the time is affecting their academic, in the worst case causes the loss of the school year, also consider that domestic violence causes emotional, physical, low self-esteem problems, lack of interest in studies etc. The methodology used in this work allowed the fulfillment of the objectives and turn its development; so we have the scientific method, deductive inductive method, analytical, synthetic method and the statistical method, such as technical bibliographic collection and the survey was also raised as a support tool that was applied to the educational trilogy, to collect information, same which he allowed depth knowledge of the problem under study.